Pengaruh Investasi Swasta dan Investasi Pemerintah Melalui Pertumbuhan Ekonomi Terhadap Kesempatan Kerja di Provinsi Bali - Diantari, Ni Putu; Wirathi, I G A P (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 4, April 2017 (pp. 472 - 676), 2017)
The purpose of this study was to analyze the effect of private investment, public investment and economic growth on employment in the province of Bali. This study used  observation data collection of non partisipan.Teknik analysis used is path analysis. The analysis showed that government investment and private investment have a positive and significant impact directly on economic growth. Government investment, private investment and economic growth also have a positive and significant impact directly on employment in the province of Bali. The indirect effect of private investment to Employment in the province of Bali through economic growth by 0010, means that the indirect effect of private investment on employment through economic growth is 1.0 percent. The value of the indirect effect of government investment on employment opportunities in the province of Bali through economic growth at 0:08, means that the indirect effect of public investment on employment through economic growth of 8.0 percent.
Keywords: investasi swasta, investasi pemerintah, pertumbuhan ekonomi, kesempatan kerja